Measuring social connectedness using air travel data. Issue 3 (6th February 2022) - Ye, Shiwei; Zhang, Guoxiong
ABSTRACT: Previous research has proposed a novel way of using Facebook friendship data to measure on-line social connectedness between county pairs and country pairs. Meanwhile, in-person social connectedness is equally, if not more important. In this paper, we provide a seemly promising way to measure in-person social connectedness using air travel data. We find that counties tend to be more socially connected if they are closer to each other or have similar income per capita, share of white people, or share of Obama voters. We also find that counties with stronger social connectedness tend to have higher bilateral trade and immigration but do not tend to have more cross-county patent citations.